KAJIAN POTENSI DAN STRATEGI PENGEMBANGAN WISATA ALAM DI KAWASAN HUTAN DENGAN TUJUAN KHUSUS (KHDTK) GUNUNG BROMO - Dwi Apriyanto; Kusnandar Kusnandar (Forestry Study Program University Of Mataram, 2020)
KHDTK Gunung Bromo Karanganyar is a state forest area whose management was handed over to Sebelas Maret University starting in 2018. The study of the potential and strategy for developing nature-based tourism is very much needed by managers to support sustainable forest management. This study aims to determine visitor ratings, analyze ADO-ODTWA, and formulate strategies for developing nature-based tourism in the KHDTK Gunung Bromo. Data was collected through structured interviews with 40 visitors, field observations, and in-depth interviews with managers, stakeholders and the community. Potential data were analyzed with ADO-ODTWA Dirjen PHKA 2003 and SWOT (Strength, Weakness, Opportunities, Threats) analysis to determine the right strategy in nature-based tourism management. The results showed the visitor's assessment of access to the location was considered good (40%) and very good (17%); cleanliness is considered sufficient (70%) and good (20%); infrastructure is considered not good (60%); the natural scenery is considered good (63%) and very good (20%). The result of the ADO-ODTWA potential value is 6.040 medium value classifications. The strategies for developing nature-based tourism in the KHDTK Gunung Bromo are: maintain high forest resource potential as a tourist attraction; developing tourism products that have competitiveness; management collaboration with investors in line with ecotourism; and conducting intensive promotional activities.